Eksistensi Perkawinan Endogami di Desa Adat Tenganan Pegringsingan Karangasem - I Gede Bagus Indra Baskara; I Made Suwitra; I Ketut Sukadana (Jurnal Konstruksi Hukum, 2021)
Bali is an area that has its own uniqueness and traditions in each village, including marriage. The traditional village of Tenganan has different characteristics and traditions from other villages, namely that the marriage system must be endogamous. This study aims to explain the status of village manners for men who marry women from outside Tenganan Village and to find out the customary sanctions for men who marry women from outside Tenganan Village. The research was designed with empirical legal research, with a sociological juridical approach, a statutory approach. The data used are primary data and secondary data. The research location is in the Tenganan Traditional Village, Manggis District, Karangasem, Bali. Data obtained using non probability sampling techniques, observations, interviews. Furthermore, the data is processed and analyzed descriptively qualitatively. The results showed that marriages between men from Tenganan Village and women from outside Tenganan Village who can still be invited in Tenganan Village are women who have caste or come from Pasek residents. Sanctions for men from Tenganan Village who marry women from outside Tenganan Village are in the form of sanctions decreasing the status of krama, from village krama to krama gumi home no longer becoming village manners and also not taking part in ngayah at Bale Agung Temple.